Advancing Critical Force Determination in Reinforced Concrete Columns: A Practical Approach: Memajukan Penentuan Gaya Kritis pada Kolom Beton Bertulang: Sebuah Pendekatan Praktis - Kulmirzayeva Gulrabo Abduganiyevna; Kosimov Turaboy Kosimovich (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to present practical solutions for determining the critical forces of eccentrically compressed reinforced concrete columns with flat buckling form, employing conventional reinforcement while considering variable joint stiffness along the rod's length. The methods involved rigorous structural analysis and experimental validation to ascertain the accuracy of the proposed approach. Results demonstrated significant advancements in accurately predicting critical forces, enhancing structural integrity, and optimizing material utilization. The implications of these findings extend to improving the safety and efficiency of reinforced concrete structures, offering valuable insights for global engineering and construction professionals. Highlights: Practical solutions for critical forces in reinforced concrete columns. Utilization of conventional reinforcement for cost-effectiveness. Consideration of variable joint stiffness for accurate predictions. Keywords: Critical Force, Eccentric Compression, Loss of Stability